Fibroblast transition to an endothelial “trans” state improves cell reprogramming efficiency - Megumi Mathison (Nature Portfolio, 2021)
Abstract Fibroblast reprogramming offers the potential for myocardial regeneration via in situ cell transdifferentiation. We explored a novel strategy leveraging endothelial cell plasticity to enhance reprogramming efficiency. Rat cardiac endothelial cells and fibroblasts were treated with Gata4, Mef2c, and Tbx5 (GMT) to assess the cardio-differentiation potential of these cells. The endothelial cell transdifferentiation factor ETV2 was transiently over-expressed in fibroblasts followed by GMT treatment to assess “trans-endothelial” cardio-differentiation. Endothelial cells treated with GMT generated more cTnT+ cells than did cardiac fibroblasts (13% ± 2% vs 4% ± 0.5%, p < 0.01). Cardiac fibroblasts treated with ETV2 demonstrated increased endothelial cell markers, and when then treated with GMT yielded greater prevalence of cells expressing cardiomyocyte markers including cTnT than did fibroblasts treated with GMT or ETV2 (10.3% ± 0.2% vs 1.7% ± 0.06% and 0.6 ± 0.03, p < 0.01). Rat cardiac fibroblasts treated with GMT + ETV2 demonstrated calcium transients upon electrical stimulation and contractility synchronous with surrounding neonatal cardiomyocytes, whereas cells treated with GMT or ETV2 alone failed to contract in co-culture experiments. Human cardiac fibroblasts treated with ETV2 and then GMT likewise demonstrated greater prevalence of cTnT expression than did cells treated with GMT alone (2.8-fold increase, p < 0.05). Cardiac fibroblast transitioning through a trans-endothelial state appears to enhance cardio-differentiation by enhancing fibroblast plasticity.